Arthur Boyd's painting materials in the 1940s: a case study of works from the Heide Museum of Modern Art Collection. Issue 1 (December 2013) - Kowalski, Vanessa; Tse, Nicole
Abstract : Recent conservation treatment of Arthur Boyd's paintings from the Heide Museum of Modern Art collection has raised questions about his studio practice and material preferences. Four paintings on muslin board from Boyd's 1943–44 'South Melbourne' series appear to use unconventional materials, which may highlight the practical realities of wartime shortages of artist paints and the alternative use of proprietary materials. The conservation treatments of Boyd's paintings initiated scientific investigations using Fourier Transform Infrared and Scanning Electron Microscopy, which is assessed in the context of Boyd's archival documents and personal correspondence. This paper presents new findings on Boyd's material choices and his intentions early in his career. Evidence suggests that Boyd used an oleoresinous varnish and experimented with new organic colourants. The use of non-traditional materials has consequently resulted in the Heide paintings exhibiting unusual ageing characteristics and by necessity, their conservation treatment. This highlights future preservation problems for 20 th century Australian works of art.